Stereoselective Synthesis of α‐Glycosyl Azides by TMSOTf‐Mediated Ring Opening of 1, 6‐Anhydro Sugars. Issue 10 (18th February 2013) - Lepage, Mathieu L.; Bodlenner, Anne; Compain, Philippe
Abstract: Access to α‐glycosyl azides in modest to high diastereoselectivity by way of TMSN3 ring‐opening of 1, 6‐anhydro sugars mediated by TMSOTf is reported. The reaction tolerates a wide variety of functional groups including alcohol, alkyne, azide and ester groups. The efficient synthesis of a pseudopentasaccharide in five steps from commercially available levoglucosan by way of a "click‐click" approach is presented to highlight the interest of the TMSN3 ring‐opening reaction. Abstract : A new route to α‐glycosyl azides by way of TMSN3 ring‐opening of 1, 6‐anhydro sugars is presented. The potential of this methodology is demonstrated by the expeditious synthesis of a pseudopentasaccharide following a "click‐click" approach.